Changes in Nematode Communities and Functional Diversity With the Conversion of Rainforest Into Rubber and Oil Palm Plantations - Krashevska, Valentyna; Kudrin, Alexey A.; Widyastuti, Rahayu; Scheu, Stefan (Frontiers in Ecology and Evolution, 2019)
Focusing on nematodes and their well-developed indices of community, ecosystem structure and function, we investigated the effects of the conversion of rainforest into rubber and oil palm plantations in Sumatra, Indonesia. Land use did not affect the total abundance of litter- and soil-dwelling nematodes, neither in riparian nor in well-drained sites. However, the rainforest nematode community differed from communities in plantations, with differences in litter being more pronounced compared to soil. In litter, fungivores and nematodes with short generation time (c-p2) increased in monoculture plantations, while that of bacterivores, herbivores, and nematodes with longer generation time and higher sensitivity to disturbances (c-p3) decreased. This indicates higher environmental pressure on nematodes in monoculture plantations than in rainforest. In soil of monoculture plantations, bacterivores and c-p3 nematodes decreased while herbivores increased. This suggests that the damage of plants by nematodes in oil palm plantations exceeds that in rainforest. Overall, nematode functional diversity indices suggest that the stability of the decomposer community is higher in rainforest compared to monoculture plantations. Importantly, functional diversity indices were much more meaningful than nematode abundance. Further, changes with land use manifested more in litter than in soil, reflecting that nematode communities in soil are buffered against changes in land use and associated environmental conditions. Therefore, to fully assess changes in the structure and functioning of decomposer systems with changes in land use, the litter layer, which often receives little attention, requires more careful consideration.